Защита от коррозии деталей ранцевых установок пожаротушения композиционными покрытиями на основе сплава Cu-Ni2. Изучение фазового состава, микроструктуры и физико-механических свойств томпаковых покрытий - Reva Ольга; Mikhalyuk Сергей; Bogdanova Валентина (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
The research of dependence the phase composition, microstructure and physic-mechanical properties of Cu-Ni films, synthesized by electrochemical sedimentation from conditions of synthesis is conducted. Course of intensive soft diffusion in nanostructured electrochemical alloys at the moment of their shaping is proved. Optimum conditions of deriving the alloys, steady against liquid corrosion in excited environments for protection the fire extinguishing installations details are defined.